The Implementation of PSAK 22 In Business Combinations: A Case Study of PT X Acquiring of PT Y - Bagaskara, Fadilah Fajar; Yanti, Harti Budi (Journal of Accounting, Management, and Economics Research (JAMER), 2025)
This study examines the application of PSAK 22 on business combinations, focusing on the acquisition of PT Y by PT X. PSAK 22 requires the acquisition method, mandating acquiring entities to measure and recognize identifiable assets, liabilities, and any goodwill from the transaction. Using a qualitative approach, the research employs in-depth interviews with key stakeholders and a literature review of financial reports and academic sources. It explores relevant accounting treatments under PSAK 22 and PSAK 65, ensuring accurate consolidation of assets and liabilities. The findings highlight challenges and advantages experienced by PT X in acquiring PT Y, providing practical insights for companies navigating similar transactions. This research underscores the alignment between PSAK 22 and the practical challenges faced by Indonesian companies, emphasizing regional and industry-specific considerations. The study offers a practical framework for companies applying PSAK 22, enriches academic discourse on business combination accounting in emerging markets, and supports policymakers in refining standards to address industry complexities. By bridging theoretical and practical perspectives, this research provides valuable guidance for improving the implementation of PSAK 22 in Indonesia and similar contexts.